Experimental investigation of tilted wick solar still using fabrics. Issue 3 (2nd September 2019) - Karthick Munisamy, T.; Mohan, A.; Veeramanikandan, M.
Abstract: Solar still is the device for solar distillation, in which water is stagnated in a basin and it is covered with glass cover. Water when exposed to solar radiation, gets evaporated and condenses under the tapered glass surface. This process removes the temporary hardness in the water, but doesn't alter the water taste. In the present work, tilted wick solar still with flat plate absorber have been fabricated and an analysis was made to review the effect of various wick material such as terrycloth, jute cloth, fur fabric and polyester cloth over the absorber plate which was inclined at 30°. In this type of stills, a huge quantity of water is not stagnated hence the vapour temperature inside the still is higher when compared to conventional stills. The experimental results show that the yield is maximum for fur fabric. Cost involved in production of water per litre in the still with respect to investment and other costs involved also presented in this article.